Lietuviškos kilmės pavardžių panašumai ir skirtumai Kuržemėje ir Latgaloje - Stafecka, Anna; Kvašytė, Regina (Acta humanitarica academiae Saulensis, 2025)
The article is dedicated to the comparative analysis of surnames of Lithuanian origin used in the Western part of Latvia, i.e. Kurzeme (including Kurzeme, Zemgale and Sēlija) and Eastern part of Latvia, i.e. Latgale, the history of which to a certain extent differs from other regions of Latvia. The giving of surnames in the regions of Latvia is different: in Kurzeme they were introduced in the first half of the 19th century. However, in Latgale surnames were introduced gradually, just as it happened in Lithuania and Poland. Nevertheless, a part of surnames in Kurzeme are older. Many of them are surnames of Lithuanian origin, because Lithuanians had apparently entered Kurzeme with surnames. Lithuanians are among the oldest and most traditional national minorities in Latvia. There were some small Lithuanian colonies in Southern and in Central Latgale. Ties with Lithuania are reflected in the surnames as well. Lithuanians have influenced both the local Latvian sub-dialects of Latgale and Kurzeme and the toponymic and anthroponymic system of these regions. Surnames of Lithuanian origin are classified into several semantic groups. Surnames motivated by names of occupations are considered to be very old. A significant number of Latvian surnames is of anthroponymic origin, usually they are derived from Christian first names. Surnames of flora and fauna semantics, as far as surnames motivated by words denoting human nature and behavior surnames form separate semantic groups. If we compare Lithuanian surnames in Kurzeme and Latgale, we can conclude that in Kurzeme there is a great variety of surnames and one surname has a small number of its owners, but in Latgale there are relatively fewer surnames of Lithuanian origin, but the number of their owners is much higher.